The autonomic nervous system: A potential link to the efficacy of acupuncture - Li, Yan-Wei; Li, Wei; Wang, Song-Tao; Gong, Yi-Nan; Dou, Bao-Min; Lyu, Zhong-Xi; Ulloa, Luis; Wang, Shen-Jun; Xu, Zhi-Fang; Guo, Yi (Frontiers in Neuroscience, 2022)
The autonomic nervous system (ANS) is a diffuse network that regulates physiological systems to maintain body homeostasis by integrating inputs from the internal and external environment, including the sympathetic, parasympathetic, and enteric nervous systems (ENS). Recent evidence suggests that ANS is one of the key neural pathways for acupuncture signal transduction, which has attracted worldwide attention in the acupuncture field. Here, we reviewed the basic and clinical research published in PubMed over the past 20 years on the effects of acupuncture on ANS regulation and homeostasis maintenance. It was found that acupuncture effectively alleviates ANS dysfunction-associated symptoms in its indications, such as migraine, depression, insomnia, functional dyspepsia, functional constipation. Acupuncture stimulation on some specific acupoints activates sensory nerve fibers, the spinal cord, and the brain. Using information integration and efferents from a complex network of autonomic nuclei of the brain, such as the insular cortex (IC), prefrontal cortex, anterior cingulate cortex (ACC), amygdala (AMG), hypothalamus, periaqueductal gray (PAG), nucleus tractus solitarius (NTS), ventrolateral medulla (VLM), nucleus ambiguus (AMB), acupuncture alleviates visceral dysfunction, inflammation via efferent autonomic nerves, and relieves pain and pain affect. The modulating pattern of sympathetic and parasympathetic nerves is associated with acupuncture stimulation on specific acupoints, intervention parameters, and disease models, and the relationships among them require further exploration. In conclusion, ANS is one of the therapeutic targets for acupuncture and mediates acupuncture’s actions, which restores homeostasis. A systemic study is needed to determine the rules and mechanisms underlying the effects of acupoint stimulation on corresponding organs mediated by specific central nervous networks and the efferent ANS.